A narrative review on subcutaneous injection components used for alopecia. (27th November 2022) - Kim, Jung Hyun
Abstract: Background: Studies reporting the development and effectiveness of topical agents for alopecia are available. However, it was difficult to demonstrate a direct advantage of subcutaneous injection rather than topical application. Since existing articles lack information, future studies are needed to solve these problems and to narrow the knowledge gap. Aims: Present article is aimed to review of the possible materials used in subcutaneous injection for alopecia with a hope for better guiding the analytic application and further evaluating the effective component for alopecia management. Methods: A wide range of clinical articles was retrieved using electronic databases to determine the possible components used in subcutaneous injection and their potential mechanism of action. Results: Eight components from 19 articles were found to be used for alopecia via subcutaneous administration. Conclusions: The current study illuminated the curative effects of possible substances and discussed the efficacy of subcutaneous injections.